Высокоэффективный газотурбинный двигатель мощностью 1 МВт - Коваль, Вячеслав Алексеевич; Беляев, В. Е.; Беляева, С. О.; Ковалева, Е. А. (Eastern-European Journal of Enterprise Technologies, 2009)
Features of the scheme and design, and also assignment the little- size engine by capacity of 1000 kw, intended for work in structure of block gas-turbine power stations and as a powerplant of a maneuverable locomotive are considered. Operational characteristics of the machine in a wide range of ambient temperatures are brought.